Strategi Pemerintah dalam Mitigasi Banjir Kecamatan Dayeuhkolot - Sitorus, David Natanael; Karniawati, Nia (Journal of Administration, Governance, and Political Issues, 2024)
Flooding is a disaster that is commonly accepted to occur in Dayeuhkolot due to the frequent floods in that area. The floods are caused by the rapid metropolitan development of the basin in the city of Bandung. This change is evident from the increase in building density and the expansion of impermeable areas, the disposal of various types of waste into rivers causing significant sedimentation in the Citarum River, and the exploitation of groundwater, leading to a yearly decline in land surface. The presence of Bandung Regency Regional Regulation No. 02 of 2013 as an effort in disaster management is expected to be a solution to the flood problems in Bandung Regency. However, since the regulation was enacted 6 years ago, floods still frequently occur to this day. This situation arises due to poor communication between the community and policymakers, as well as inadequate resources for the implementation of the regulation. The research method used is descriptive with a qualitative approach. The researcher employs a qualitative descriptive approach, focusing on the problems and understanding them by gathering information from sources. Based on the discussion results, the implementation of the Flood Disaster Mitigation Policy by BPBD Dayeuhkolot Village, Bandung Regency has not been maximized, and there are still problems and obstacles faced in its execution. This is indicated by issues found in Flood Disaster Prevention, Flood Disaster Emergency Response, and Flood Disaster Rehabilitation and Reconstruction.